THE INFLUENCE OF MIND MAPPING MODEL AND MOTIVATIONON THE LEARNING OUTCOMES OF PPKN CLASS III STUDENTS OF SDN 05 MESJID LAMA, BATU BARA REGENCY 2020/2021 - Annisa Suci Lestari; Ramli Nur; Dede Ruslan (Sensei International Journal of Education and Linguistic, 2021)
This study was based background by educational purposes to prepare individuals who have the ability and skills become more good. The objectives of this study were (1) To determine the effect of the Mind Mapping learning model on the motivation and learning outcomes of PPKn in grade III students at SDN 05 Mesjid Lama, Batu Bara Regency. (2) To determine the comparison of students' motivation and learning outcomes of PPKn by applying the Mind Mapping learning model with a conventional learning model for grade III students at SDN 05 Mesjid Lama, Batu Bara Regency. (3) To determine the interaction between the Mind Mapping learning model and learning motivation on the learning outcomes of PPKn in grade III students at SDN 05 Mesjid Lama, Batu Bara Regency. This research uses a quantitative approach. Data analysis using Tuckey-test. The results showed that (1) There was an effect of the Mind Mapping learning model on the learning outcomes of PPKn in grade III students at SDN 05 Mesjid Lama, Batu Bara Regency. (2) There is an effect of student motivation on student PPKn learning outcomes in grade III students at SDN 05 Mesjid Lama, Batu Bara Regency. (3) There is an interaction between the Mind Mapping learning model and learning motivation on PPKn learning outcomes in grade III students at SDN 05 Mesjid Lama, Batu Bara Regency